The First Report of a Fully Sequenced Resistance Plasmid from Shigella boydii - Wang, Li; Liu, Lei; Liu, Dong; Yin, Zhe; Feng, Jiao; Zhang, Defu; Fang, Haihong; Qiu, Yefeng; Chen, Weijun; Yang, Ruisheng; Wang, Jinglin; Fa, Yunzhi; et al. (Frontiers in Microbiology, 2016)
The purpose of this study was to characterize mechanisms of plasmid-mediated antimicrobial resistance in Shigella boydii. S. boydii strain 2246 with resistance to ciprofloxacin, ceftriaxone and azithromycin was isolated from a human case of watery diarrhea in a Chinese public hospital. Resistance in strain 2246 to ceftriaxone and azithromycin was attributable to the presence of blaCTX-M-14, and erm(B) and mph(A), respectively, which were co-located on a multidrug-resistant (MDR) plasmid p2246-CTXM. p2246-CTXM represented a novel IncFII-type MDR plasmid with a very complex chimera structure. Its master backbone was genetically closely related to the R100 plasmid, but p2246-CTXM had evolved to integrate additional R100-unrelated backbone regions as well as massive exogenous mobile elements that carried multiple resistance determinants. In p2246-CTXM, erm(B) together with its leading peptide gene erm(C), mph(A) together with its regulatory genes mrx and mphR(A), and blaCTX-M-14 were captured by three different mobile elements Tn6295, the IS26-mph(A)- mrx-mphR(A)-IS6100 unit, and a truncated ISEcp1-blaCTX-M-14-IS903D-iroN transposition unit, respectively, all of which were harbored in a large Tn3-family transposon Tn6285. p2246-CTXM still carried additional resistance determinants mer (mercury resistance), aacA4 (aminoglycoside resistance), cmlA1 (chloramphenicol resistance) and qacED1 (quaternary ammonium compound resistance). This is the first report of identifying a clinical S. boydii strain simultaneously resistant to ciprofloxacin, ceftriaxone and azithromycin, and determining the complete sequence of a resistance plasmid from S. boydii.